Metode Penerjemahan Al-Qur‟an Dan Kritik Muhammad Thalib Terhadap Q.S An-Nisaa: 34 Versi Departemen Agama - Rooby Pangestu Hari Mulyo (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2022)
Abstract The Qur'an is a divine kalam revealed to the Prophet Muhammad pbuh, which is a mandatory handle for its adherents. In its development, many scholars interpreted the content of the Qur'an, not to be missed, the State of Indonesia as a country with the majority of Muslims also participated in interpreting the Qur'an carried out by the government which was carried out by the Ministry of Agriculture. The emergence of the Qur'an Translation from the Ministry of Agriculture caused a reaction from the Indonesian Mujahideen Council (MMI). Muhammad Talib, who created a work entitled Al-Qur'anul Karim: Tarjamah Tafsiriyah 'understanding the Meaning of the Qur'an more Easily, Quickly and Precisely', is a form of criticism of the government. One of the translations of the criticized verse is the letter an-nisaa: 34. Muhammad Talib in translating the Qur'an, namely by the Tafsiriyah method.